Bushmeat hunting, retaliatory killing, habitat degradation and exotic species as threats to Fosa (Cryptoprocta ferox) conservation - Merson, S (2017)
Large carnivores are in global decline, chiefly resultant of anthropogenic persecution, habitat reduction and disturbance. Fosas represent Madagascar’s largest carnivore, occupying much of the island's forest. This thesis examines the threats of bushmeat hunting, retaliatory killing, habitat alteration and exotic species using sociological and remote-sensing methodologies. Habitat degradation was not associated with reduced fosa occupancy, indicating some resilience within large, contiguous forests. However, competition with exotic species (cats, dogs) was associated with reduced fosa occupancy and potential temporal shifts towards greater nocturnality. Poor households were more likely to consume protected species. Conversely, wealthier households consumed more fish and eel. This pattern is reflected in Malagasy reported taste preference to consume domesticated animals and certain legally hunted wild species. Protected areas were not associated with reduced protected species consumption. Fosas' predation was a major cause of rural poultry mortality. Predation was more likely to occur in deciduous forests, in the dry season, during the evening. Fosa predation, and lower education was associated with negative Malagasy attitudes. Wealthy households, and those that had experienced fosa predation were most likely to retaliatory kill a fosa. Strategies to safeguard fosas' long-term persistence should seek to improve domestic husbandry, build robust coops with the use of watchdogs, promote education, and reduce exotic species abundance.